2001
DOI: 10.2144/01304pf01
|View full text |Cite
|
Sign up to set email alerts
|

Poly (ADP-Ribose) Polymerase Cleavage Monitored In Situ in Apoptotic Cells

Abstract: During apoptosis, the activation of a family of cysteine proteases, or caspases, results in proteolytic cleavage of numerous substrates. Antibody probes specific for neoepitopes on protein fragments generated by caspase cleavage provide a means to monitor caspase activity at the level of the individual cell. Poly (ADP-ribose) polymerase (PARP), a nuclear enzyme involved in DNA repair, is a well-known substrate for caspase-3 cleavage during apoptosis. Its cleavage is considered to be a hallmark of apoptosis. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…This was associated with increased cytochrome c translocation in vivo and increased activation of caspase-3 here, as well as in several studies (42,43). The irradiationinduced increase in cytochrome c translocation, together with increased cleavage of the caspase-3 substrate, PARP, and increased TUNEL-labeling in vivo and in vitro are considered to be reliable indicators of apoptosis (44,45). Taken together the data suggest that exposure of rats to ␥-irradiation leads to apoptosis in hippocampus, providing an explanation for the marked cell loss observed in hippocampus following irradiation (46).…”
Section: Figmentioning
confidence: 57%
“…This was associated with increased cytochrome c translocation in vivo and increased activation of caspase-3 here, as well as in several studies (42,43). The irradiationinduced increase in cytochrome c translocation, together with increased cleavage of the caspase-3 substrate, PARP, and increased TUNEL-labeling in vivo and in vitro are considered to be reliable indicators of apoptosis (44,45). Taken together the data suggest that exposure of rats to ␥-irradiation leads to apoptosis in hippocampus, providing an explanation for the marked cell loss observed in hippocampus following irradiation (46).…”
Section: Figmentioning
confidence: 57%
“…We have previously reported that cleavage of PARP was increased in entorhinal cortex of lipopolysaccharide-treated rats, and this change was accompanied by changes in morphology of cells that were indicative of cell death (20). Indeed cleavage of PARP has been considered to be a reliable marked of apoptosis (49,50). Significantly, we observed that these lipopolysaccharide-induced changes were blocked by caspase-1 inhibition pinpointing a role for IL-1␤ in the cascade of events leading to cell death (8).…”
Section: Fig 3 the Age-related Increase In Caspase-3 Activity Is MImentioning
confidence: 58%
“…When caspases cleave proteins, they generate novel peptide ends that could represent neoepitopes. Generation of antibodies to such neoepitopes has been reported for several caspase protein substrates, including caspases themselves (Srinivasan et al 1998;Knaapen et al 1999;Tanaka et al 2000), and for other substrates, such as PARP (O'Brien et al 2001) and cytokeratin 18 (Caulin et al 1997;Leers et al 1999). The use of such antibodies for immunohistochemistry could represent a specific method for detection of apoptotic cells in archival materials if the substrates are present in many cells and if the neoepitopes are accessible and preserved with routine formaldehyde fixation and paraffin embedding.…”
mentioning
confidence: 99%